Kinetic and mechanistic study of the reaction of OH radicals with methylated benzenes: 1, 4-dimethyl-, 1, 3, 5-trimethyl-, 1, 2, 4, 5-, 1, 2, 3, 5- and 1, 2, 3, 4-tetramethyl-, pentamethyl-, and hexamethylbenzene1. Issue 19 (21st May 2015) - Alarcón, P.; Bohn, B.; Zetzsch, C.
<x xml:space="preserve">Abstract</x> Reversible formation of OH-adducts with methylated benzenes.